A drill pipe joint wear-resistant belt flux-cored welding wire
By using specific composition flux-core welding wires in the drill pipe joint wear belt for arc welding, high hardness and wear resistance surfacing alloys are generated, and cracking of existing wear-resistant belt materials under high stress wear conditions is solved. Problems and severe wear problems on the inner wall of the casing achieve longer service time and lower wear.
Patent Information
- Application Number
- CN202410779291.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-17
AI Technical Summary
The wear-resistant belt materials of existing drill pipe joints are prone to cracking under high stress wear conditions, resulting in failure and scrapping of wear-resistant belts and causing severe wear to the inner wall of the casing.
A drill pipe joint wear-resistant flux-core welding wire, whose flux-core powder composition includes iron titanium, chromium carbide, ferromolybdenum, manganese, ferrosilicon, graphite, ferrovana and sodium fluoride, and high hardness is generated through arc welding process. , surfacing alloy with wear resistance and good friction reduction.
The high hardness and wear resistance of the surfacing alloy are achieved, while reducing wear on the inner wall of the casing and extending the service time of the casing.
Smart Images

Figure CN118664172B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding materials, in particular to a drill pipe joint wear-resistant belt flux-cored welding wire. Background Art
[0002] Drill pipe is one of the important tools for oil and gas resource exploration and exploitation. Drilling is achieved by transmitting the torque of the drilling rig to the drill bit. During the drilling process, the outer diameter of the drill pipe joint is larger than the drill pipe itself. The drill pipe joint first rubs against the well wall or the inner wall of the casing, so the drill pipe joint becomes the most severely worn part of the drill pipe. In order to solve this problem, it is necessary to weld a layer of cladding metal on the drill pipe joint to protect the drill pipe joint. This layer of cladding metal is called the drill pipe joint wear belt. The wear belt can isolate the drill pipe joint from the well wall or the inner wall of the casing, effectively reducing the wear of the drill pipe joint by rock particles.
[0003] Arc surfacing with flux-cored wire is a common preparation technology for drill pipe joint hardbands. According to different working environments and performance, the flux core composition is reasonably designed, and arc surfacing is performed on the surface of the parent material to obtain a surfacing layer with high hardness, high wear resistance and corrosion resistance. Arc surfacing with flux-cored wire has a wide range of applications, high production efficiency, low cost, simple equipment, and good on-site construction performance. It is the preferred surfacing process for hardbands for drilling tool companies and oil fields. Developing a high-performance flux-cored wire so that the cladding metal obtained after surfacing has good wear resistance, a low friction coefficient and good friction reduction is a key measure to solve the wear of drill pipe joints and the inner wall of casing.
[0004] At present, the commonly used wear-resistant belt materials are tungsten carbide wear-resistant belt and high-chromium iron-based wear-resistant belt. Tungsten carbide wear-resistant belt has good hardness and wear resistance due to its high hardness and high wear-resistant hard alloy tungsten carbide phase; high volume fraction of coarse hard phase primary carbide M7C3 will precipitate in the microstructure of high-chromium iron-based alloy wear-resistant belt. The precipitation of these hard phases significantly improves the hardness and wear resistance of the wear-resistant belt, which can effectively protect the drill pipe joint and prevent the drill pipe joint from serious wear. However, it is precisely because of the high hardness and wear resistance of these hard phases that these materials can also cause serious wear on the inner wall of the casing, and even wear through the casing and scrap it; it is also easy to crack under high stress wear conditions, causing the wear-resistant belt to fail and be scrapped. Carbide-reinforced iron-chromium alloy is a new type of wear-resistant belt material. It precipitates fine hard carbide phases on the martensitic matrix. These dispersed carbides can significantly improve the hardness and wear resistance of the alloy. Moreover, the martensitic matrix plus fine carbides can also show good friction reduction, reduce the wear and cracking of the inner wall of the casing, and extend the service life of the casing. Common carbides include TiC, NbC, MoC, VC, and WC. Among them, TiC becomes the strengthening phase of iron-based, aluminum-based, titanium-based, copper-based, and cobalt-based alloys due to its high hardness, excellent wear resistance, corrosion resistance, and thermal stability. There are two ways to precipitate TiC in the alloy. One is to directly add TiC to the flux-cored wire, and the other is to generate TiC through the in-situ reaction of titanium iron and graphite in the flux-cored wire. The surfacing alloy obtained by in-situ generation of TiC has better forming and better mechanical properties. However, it is inevitable that both methods will produce porosity defects. Therefore, it is necessary to change the composition of the flux-cored welding wire to suppress the generation of welding porosity defects and improve the surfacing processability of the wear-resistant belt. Summary of the invention
[0005] Based on the above content, the purpose of the present invention is to provide a drill pipe joint wear-resistant belt flux-cored welding wire. The flux-cored welding wire provided by the present invention is obtained by arc surfacing. The surfacing alloy not only has good surfacing processability, beautiful weld formation, and a small number of surface pores, but also has high hardness, high wear resistance and good friction reduction, reducing the wear of the wear-resistant belt on the casing.
[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a core powder, comprising the following components in percentage by mass: 20-30% ferrotitanium, 47-57% chromium carbide, 4-12% ferromolybdenum, 4-10% manganese, 4-10% ferrosilicon, 2-8% graphite, 2-8% ferrovanadium, 1-6% sodium fluoride, and the balance is iron powder.
[0007] Preferably, the following components are included in percentage by mass: 24-26% ferrotitanium, 52-55% chromium carbide, 6-8% ferromolybdenum, 6-8% manganese, 6-8% ferrosilicon, 4-6% graphite, 3-6% ferrovanadium, 2-4% sodium fluoride, and the remainder is iron powder.
[0008] Preferably, the particle size of the titanium iron is 30-50 mesh; the particle sizes of the chromium carbide, ferromolybdenum and ferrovanadium are all 80-100 mesh; the particle size of manganese is 60-80 mesh; the particle size of the ferrosilicon is 70-90 mesh; the particle size of the graphite is 40-60 mesh; and the particle size of the sodium fluoride is 50-70 mesh.
[0009] Preferably, the mass fraction of titanium in the titanium iron is 70%; the mass fraction of chromium in the chromium carbide is 87%, and the mass fraction of carbon is 8%; the mass fraction of molybdenum in the ferromolybdenum powder is 60%; the mass fraction of silicon in the ferrosilicon is 75%; the mass fraction of vanadium in the ferrovanadium powder is 50%; the mass fraction of manganese in the manganese raw material is greater than 90%; and the mass fraction of carbon in the graphite is greater than 99.5%.
[0010] The present invention also provides a drill pipe joint wear-resistant belt flux-cored welding wire, the raw material of which includes the flux-cored powder described in the above technical solution.
[0011] Preferably, the filling rate of the flux-cored powder in the flux-cored welding wire is 22-30%.
[0012] The present invention also provides a welding method for reducing welding porosity of the drill pipe joint wear-resistant belt, which uses the drill pipe joint wear-resistant belt flux-cored welding wire described in the above technical solution for welding; the welding process is an arc surfacing process.
[0013] Preferably, the arc surfacing process parameters are: voltage: 21-24V, current: 280-300A, wire feeding speed: 8-9m / min, atmosphere: 80% Ar+20% CO2 mixed gas, gas flow: 15-20L / min, wire elongation: 15-20mm.
[0014] Preferably, after the welding is completed, the mass percentage of alloy elements in the obtained cladding metal is within the following range: C: 1.40-2.22%, Cr: 11.0-13.4%, Ti: 4.00-7.50%, Si: 1.20-2.00%, Mn: 1.20-2.00%, Mo: 1.20-2.00%, V: 0.20-0.80%, Al: 0.20-1.00%, Fe: balance.
[0015] Beneficial technical effects:
[0016] The flux-cored welding wire for the drill pipe joint wear-resistant belt provided by the present invention meets the use performance of the new wear-resistant belt material, meets the requirements of high hardness and excellent wear resistance, and can have good friction reduction and reduce the wear on the inner wall of the casing.
[0017] The microstructure of the alloy obtained by arc surfacing with the flux-cored welding wire for the drill pipe joint wear-resistant belt of the present invention consists of martensite, austenite, hard phase TiC and eutectic carbide M7C3. The TiC generated in situ in the alloy can refine the grains of martensite, and the reduction of martensite grains can play a role in fine grain strengthening, which not only improves the strength and hardness of martensite, but also improves the plasticity of martensite, so that the matrix microstructure shows comprehensive toughness. At the same time, the dispersed hard phase TiC has a small size and a high bonding strength with martensite, which significantly improves the wear resistance of the matrix. The fine grain structure and the fine hard phase TiC show good friction reduction, which can reduce the wear of the wear-resistant belt on the casing and extend the service life of the casing.
[0018] The flux-cored welding wire arc surfacing for the drill pipe joint wear-resistant belt of the present invention has good processability, good weld formation, a small number of surface pores, a small amount of spatter, and a high metallurgical bonding strength between the surfacing alloy and the parent material. The flux-cored welding wire for the drill pipe joint wear-resistant belt of the present invention adopts a method of in-situ generation of TiC. Compared with the method of directly adding TiC to the flux-cored welding wire, the in-situ generated TiC has better wettability with the matrix, and the bonding strength between the in-situ TiC and the matrix is higher, which has a more significant effect on improving the hardness and wear resistance of the surfacing alloy. At the same time, by using titanium iron and graphite to in-situ generate TiC, the cost of the flux-cored powder is lower, which is more suitable for large-scale and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is the macroscopic morphology of the surfacing alloy of Example 1.
[0021] Figure 2 This is the SEM image of the microstructure of the surfacing alloy in Example 1.
[0022] Figure 3 This is the macroscopic morphology of the surfacing alloy of Example 2.
[0023] Figure 4 This is the SEM image of the microstructure of the surfacing alloy of Example 2. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The invention provides a core powder, which comprises the following components in percentage by mass: 20-30% of ferrotitanium, 47-57% of chromium carbide, 4-12% of ferromolybdenum, 4-10% of manganese, 4-10% of ferrosilicon, 2-8% of graphite, 2-8% of ferrovanadium, 1-6% of sodium fluoride, and the balance is iron powder.
[0030] In some embodiments, the core powder includes the following components in percentage by mass: 22-28% ferrotitanium, 53-57% chromium carbide, 6-10% ferromolybdenum, 5-9% manganese; 5-9% ferrosilicon, 3-7% graphite, 3-7% ferrovanadium, 1-5% sodium fluoride, and the remainder is iron powder.
[0031] In some embodiments, the core powder includes the following components in percentage by mass: 24-26% ferrotitanium, 52-55% chromium carbide, 6-8% ferromolybdenum, 6-8% manganese; 6-8% ferrosilicon, 4-6% graphite, 3-6% ferrovanadium, 2-4% sodium fluoride, and the remainder is iron powder.
[0032] In some embodiments, the particle size of the titanium iron is 30-50 mesh; the particle sizes of the chromium carbide, ferromolybdenum and ferrovanadium are all 80-100 mesh; the particle size of manganese is 60-80 mesh; the particle size of the ferrosilicon is 70-90 mesh; the particle size of the graphite is 40-60 mesh; and the particle size of the sodium fluoride is 50-70 mesh.
[0033] In some embodiments, the mass fraction of titanium in the titanium iron is 70%; the mass fraction of chromium in the chromium carbide is 87%, and the mass fraction of carbon is 8%; the mass fraction of molybdenum in the ferromolybdenum powder is 60%; the mass fraction of silicon in the ferrosilicon is 75%; the mass fraction of vanadium in the ferrovanadium powder is 50%; the mass fraction of manganese in the manganese raw material is greater than 90%; and the mass fraction of carbon in the graphite is greater than 99.5%.
[0034] In some embodiments, the raw material of the drug core powder needs to be dried before use; the drying temperature is 150° C. and the drying time is 2 hours.
[0035] The present invention also provides a drill pipe joint wear-resistant belt flux-cored welding wire, the raw material of which includes the flux-cored powder described in the above technical solution.
[0036] In some embodiments, the drill pipe joint wear-resistant belt flux-cored welding wire is composed of a cold-rolled annealed carbon steel strip wrapped with the flux-cored powder described in the above technical solution.
[0037] In some embodiments, the filling rate of the flux-cored powder in the flux-cored welding wire is 22-30%, preferably 24-28%, and more preferably 26-28%.
[0038] In some embodiments, when the filling rate of the core powder in the drill pipe joint wear-resistant belt cored welding wire is 26-28%, the mass percentage of the core components is: ferrotitanium: 24-26%, chromium carbide: 52-55%, ferromolybdenum: 6-8%, manganese: 6-8%, ferrosilicon: 6-8%, graphite: 4-6%, ferrovanadium: 4-6%, sodium fluoride: 2-4%, and the balance is reduced iron powder.
[0039] In some embodiments, the method for preparing the drill pipe joint wear-resistant belt flux-cored welding wire comprises the following steps:
[0040] (1) Powder selection and powder drying: Select alloy powder according to the above core composition and dry each powder in advance. The drying equipment is a vacuum drying oven, the drying temperature is 150°C, and the drying time is 2 hours.
[0041] (2) Powder screening: In order to ensure the consistency of the particle size of the same powder, each powder needs to be screened through a sieve.
[0042] (3) Powder preparation and mixing: Powder preparation is carried out according to the kilograms of each flux-cored welding wire trial, the filling rate and the mass percentage of each powder. After the powder preparation is completed, the different powders need to be mixed evenly to ensure that the components in the flux-cored welding wire are uniform.
[0043] (4) Strip selection: Select cold-rolled annealed carbon steel strip with a thickness of 0.5 mm and a width of 12 mm.
[0044] (5) Drawing: The steel belt passes through the first few rollers and changes from a flat surface to a U-shape. At this time, the prepared core powder is fed into the U-shaped steel belt through a conveyor belt. After the U-shaped steel belt carrying the powder passes through the next few groups of rollers, the steel belt changes from a U-shape to an O-shape, and the steel belt closes, tightly wrapping the core powder.
[0045] (6) Diameter reduction and packaging: The drawn flux-cored welding wire is passed through a drawing die of a certain diameter to finally reach the required diameter size of the finished product. The reduced diameter flux-cored welding wire is loaded into an I-shaped wheel and sealed for storage before use.
[0046] The present invention also provides a welding method for reducing welding porosity of the drill pipe joint wear-resistant belt, which uses the drill pipe joint wear-resistant belt flux-cored welding wire described in the above technical solution for welding; the welding process is an arc surfacing process.
[0047] In some embodiments, the arc surfacing process parameters are: voltage: 21-24V, current: 280-300A, wire feeding speed: 8-9m / min, atmosphere: 80% Ar+20% CO2 mixed gas, gas flow: 15-20L / min, wire elongation: 15-20mm.
[0048] In some embodiments, after the welding is completed, the mass percentage of alloy elements in the obtained cladding metal is within the following range: C: 1.40-2.22%, Cr: 11.0-13.4%, Ti: 4.00-7.50%, Si: 1.20-2.00%, Mn: 1.20-2.00%, Mo: 1.20-2.00%, V: 0.20-0.80%, Al: 0.20-1.00%, Fe: balance.
[0049] In some embodiments, after the welding is completed, the mass percentage of alloy elements in the obtained cladding metal is within the following range: C: 1.65-2.00%, Cr: 11.6-12.9%, Ti: 4.50-7.00%, Si: 1.40-1.80%, Mn: 1.40-1.80%, Mo: 1.42-1.80%, V: 0.40-0.70%, Al: 0.30-0.80%, Fe: balance.
[0050] In some embodiments, after the welding is completed, the mass percentage of alloy elements in the obtained cladding metal is within the following ranges: C: 1.68-1.84%, Cr: 12.3-13.4%, Ti: 4.90-6.00%, Si: 1.55-1.75%, Mn: 1.60-1.75%, Mo: 1.45-1.64%, V: 0.50-0.62%, Al: 0.62-0.70%, Fe: balance.
[0051] In the present invention, various powders act as follows:
[0052] Ferrotitanium: Titanium element is transitioned to the weld metal. Titanium combines with carbon in the weld pool to form high-hardness titanium carbide, thereby improving the wear resistance of the surfacing alloy. The wear resistance of the surfacing alloy increases with the increase of titanium content, but too high titanium content will consume carbon in the matrix, resulting in a weakening of the solid solution strengthening effect of carbon in the martensite in the matrix, reducing the hardness of the martensite, resulting in a decrease in the hardness and wear resistance of the surfacing alloy. Too high titanium content will also cause the volume fraction of precipitated TiC to be too high, and the size of the precipitated TiC will increase, causing cracks and pore defects in the surfacing metal. Therefore, the mass percentage of titanium element in the surfacing alloy designed by the present invention is 4.90-6.00%, and the mass percentage of ferrotitanium added to the corresponding flux-cored welding wire is 24-26%.
[0053] Chromium carbide: Chromium and carbon elements are transferred to the weld metal. Chromium can improve hardenability, promote the transformation of austenite to martensite, and improve the hardness and wear resistance of the structure. Chromium can also improve the corrosion resistance and thermal fatigue resistance of the cladding alloy. Too high chromium content will generate coarse primary carbides M7C3, M 23 C6 and other hard phases reduce the friction reduction of the wear-resistant belt and increase the wear of the wear-resistant belt on the casing. Therefore, the mass percentage of chromium in the cladding alloy of the present invention is designed to be 12.30-13.40%, and the mass percentage of chromium carbide added to the corresponding flux-cored wire is 52-55%.
[0054] Ferro-molybdenum: Molybdenum element is transferred to the weld metal. Molybdenum element can combine with carbon to form MoC dispersed on the austenite grain boundary, which improves the hardness and wear resistance of the alloy. When the molybdenum content is greater than 3%, the plasticity and toughness of the alloy will be reduced. Therefore, the mass percentage of molybdenum element in the surfacing alloy designed by the present invention is 1.45-1.64%, and the mass percentage of ferro-molybdenum added to the corresponding flux-cored wire is 6-8%.
[0055] Electrolytic manganese: Manganese is a strong deoxidizer that can reduce the oxygen content in the molten pool, reduce the viscosity of the molten pool, improve weld formation, and reduce the generation of pore defects caused by the existence of the molten pool for too long. However, too high a manganese content will increase the temper brittleness of the alloy. The mass percentage of manganese added to the corresponding flux-cored wire is 6-8%.
[0056] Ferrosilicon: Silicon can not only increase the yield strength and yield strength ratio of the alloy, but also improve the fluidity of the molten pool.
[0057] Ferrovanadium: reduces the austenite phase area and improves hardenability.
[0058] Graphite: A strong deoxidizer that also transfers carbon to the weld metal, ensuring that there is enough carbon in the weld to combine with titanium to form titanium carbide.
[0059] Sodium fluoride: It has the function of slag formation. The slag produced during welding can protect the molten pool. At the same time, fluoride ions can reduce the hydrogen partial pressure and prevent the formation of hydrogen pores in the weld.
[0060] Reduced iron powder: fill the balance.
[0061] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the examples, but the content of the present invention is not limited to the following examples. The same parts in each embodiment are described as follows:
[0062] In the examples, all the raw materials used can be obtained through commercial sources.
[0063] In the embodiment, the outer skin of the flux-cored welding wire is made of cold-rolled annealed carbon steel strip, and the thickness of the steel strip is 0.5 mm and the width is 12 mm. The core components of the flux-cored welding wire are specifically described in the embodiment. The steel strip is rolled into a U-shape after passing through the rollers, and the various powders in the formula are weighed, dried, and mixed in advance according to the designed proportions, and then mechanically added to the steel strip. The U-shaped steel strip is closed after passing through subsequent rollers. The closed steel strip is repeatedly pulled and reduced in diameter using a reducing device to form a flux-cored welding wire with a diameter of 1.6 mm. An iron-based flux-cored welding wire for a wear-resistant belt of a drill pipe joint is obtained.
[0064] In the core powder, the particle size of titanium iron powder is 30-50 meshes; the particle size of chromium carbide powder, molybdenum iron powder and vanadium iron powder is 80-100 meshes; the particle size of electrolytic manganese is 60-80 meshes; the particle size of ferrosilicon powder is 70-90 meshes; the particle size of graphite is 40-60 meshes; and the particle size of sodium fluoride is 50-70 meshes.
[0065] In the core powder, the mass fraction of titanium in the titanium ferropowder is 70%; the mass fraction of chromium in the chromium carbide powder is 87%, and the mass fraction of carbon is 8%; the mass fraction of molybdenum in the molybdenum ferropowder is 60%; the mass fraction of silicon in the ferrosilicon is 75%; the mass fraction of vanadium in the vanadium ferropowder is 50%; the mass fraction of manganese in the electrolytic manganese metal is greater than 90%; and the mass fraction of carbon in the graphite is greater than 99.5%.
[0066] The surfacing alloy was prepared by 80% Ar + 20% CO2 mixed gas shielded arc surfacing process, and the welding process parameters were: voltage: 21-24 V; current: 280-300 A; wire feeding speed: 8-9 m / min; atmosphere: 80% Ar + 20% CO2 mixed gas; gas flow: 15-20 L / min; wire elongation: 15-20 mm.
[0067] The hardness test, abrasive wear test and friction wear test were carried out on the surfacing alloy prepared in the embodiment. The specific steps of the test are as follows:
[0068] The Rockwell hardness of the cladding alloy was tested using an HR-150A electric Brinell hardness tester. The indenter of the hardness tester is a diamond cone indenter, the load is 150kg, the loading time is 5s, and the recovery time is 3s. The distance between two adjacent test points is 5mm, and the number of test points is 9. The final hardness of the cladding alloy is the average value of the data of the 9 test points.
[0069] The abrasive wear test was conducted using an MLS-225 wet sand rubber wheel abrasive wear tester. The size of the wear sample was 57mm×25mm×10mm. The main test parameters included: the diameter of the rubber wheel was 176mm, the speed of the rubber wheel was 240rpm, the hardness of the rubber wheel was 60 Shore hardness, the abrasive was quartz sand of 40-70 mesh, the loading load was 100N, 1000g of water and 1500g of quartz sand were added during the test. Before each test, a 5-minute pre-grinding was performed to avoid the influence of the surface roughness of the sample on the wear result. After pre-grinding, the sample was weighed as the weight before wear; after 30 minutes of fine grinding, the sample was weighed as the weight after wear, and the weight loss of the test was obtained by subtracting the two. Before and after each wear test, the sample was immersed in an ethanol solution, ultrasonically cleaned, and dried with a hair dryer. The sample was weighed using a Beijing Sartorius precision balance, and the weight was accurate to 0.0001g. Three tests were conducted on each sample, and the average value of the sample wear loss weight was taken as the reference standard for wear resistance.
[0070] The friction and wear test was carried out using an MM-200 dry sliding wear tester. The size of the wear specimen is 19mm×12mm×12mm, and a load of 196N is applied on the specimen. The grinding ring is used as a friction pair, the material is GCr15, the hardness is 58-61HRC, the size is R 20mm×10mm, the grinding ring is in direct contact with the specimen, and the transmission device drives the grinding ring to rotate at a speed of 200r / min. The test time is 2h. In a dry environment at room temperature, in order to reduce the error of the experiment, each specimen was tested three times. After the test, a laser confocal microscope was used to observe the three-dimensional morphology of the specimen wear scar and calculate the wear volume of the specimen. The specimen wear rate is calculated using the following formula:
[0071] W=ΔV / (F×D)
[0072] Among them, W (mm 3 ×N -1 ×m -1 ) is the wear rate of the sample, ΔV (mm 3 ) is the wear volume, F (N) is the test load, and D (m) is the sliding distance.
[0073] Example 1
[0074] Take 0.78 kg of ferrotitanium, 1.29 kg of chromium carbide, 0.14 kg of ferromolybdenum, 0.11 kg of electrolytic manganese, 0.14 kg of ferrosilicon, 0.18 kg of graphite, 0.05 kg of ferrovanadium, 0.10 kg of sodium fluoride, and 0.07 kg of reduced iron powder. Mix the prepared powders evenly and add them into the U-shaped steel belt groove, with a filling rate of 26%.
[0075] The cladding alloy is prepared according to the above cladding process, and the mass percentage of alloy elements in the obtained cladding metal is C: 1.72%; Cr: 12.5%; Ti: 5.10%; Si: 1.42%; Mn: 1.52%; Mo: 1.40%; V: 0.30%; Al: 0.42%; Fe: balance.
[0076] The surfacing process produces less spatter, the weld is beautiful, the surface of the surfacing alloy is bright, free of pores, high flatness, free of cracks and oxidation. The microstructure of the surfacing alloy is composed of martensite, austenite, TiC and eutectic carbide M7C3. Figure 1 and Figure 2 ).
[0077] The Rockwell hardness of the cladding alloy is 62.6HRC. In the abrasive wear test, the weight loss is 0.2651g. In the friction wear test, the wear rate is 8.61×10 -8 mm 3 ×N -1 ×m -1 , the friction coefficient is 0.54.
[0078] Example 2
[0079] Take 0.78 kg of ferrotitanium, 1.32 kg of chromium carbide, 0.19 kg of ferromolybdenum, 0.18 kg of electrolytic manganese, 0.17 kg of ferrosilicon, 0.07 kg of graphite, 0.06 kg of ferrovanadium, 0.10 kg of sodium fluoride, and 0.24 kg of reduced iron powder. Mix the prepared powders evenly and add them into the U-shaped steel belt groove, with a filling rate of 28%.
[0080] The cladding alloy is prepared according to the above cladding process, and the mass percentage of alloy elements in the obtained cladding metal is C: 1.85%; Cr: 13.6%; Ti: 5.88%; Si: 1.82%; Mn: 1.76%; Mo: 1.63%; V: 0.48%; Al: 0.65%; Fe: balance.
[0081] The surfacing process produces less spatter, the weld is beautiful, the surface of the surfacing alloy is bright, without obvious pores, high flatness, no cracks and no oxidation. The microstructure of the surfacing alloy is composed of martensite, austenite, TiC and eutectic carbide M7C3. Figure 3 and Figure 4 ).
[0082] The Rockwell hardness of the cladding alloy is 63.1HRC. In the abrasive wear test, the weight loss is 0.2048g. In the friction wear test, the wear rate is 7.82×10 -8 mm 3 ×N -1 ×m -1 , the friction coefficient is 0.49.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A drug core powder, characterized in that: The invention comprises the following components in percentage by mass: 20-30% ferrotitanium, 47-57% chromium carbide, 4-12% ferromolybdenum, 4-10% manganese, 4-10% ferrosilicon, 2-8% graphite, 2-8% ferrovanadium, 1-6% sodium fluoride, and the balance is iron powder; The mass fraction of titanium in the ferrotitanium is 70%; the mass fraction of chromium in the chromium carbide is 87%, and the mass fraction of carbon is 8%; the mass fraction of molybdenum in the ferromolybdenum powder is 60%; the mass fraction of silicon in the ferrosilicon is 75%; the mass fraction of vanadium in the ferrovanadium powder is 50%; the mass fraction of manganese in the manganese raw material is greater than 90%; and the mass fraction of carbon in the graphite is greater than 99.5%.
2. The drug core powder according to claim 1, characterized in that: The invention comprises the following components in percentage by mass: 24-26% of ferrotitanium, 52-55% of chromium carbide, 6-8% of ferromolybdenum, 6-8% of manganese, 6-8% of ferrosilicon, 4-6% of graphite, 3-6% of ferrovanadium, 2-4% of sodium fluoride, and the balance is iron powder.
3. The drug core powder according to claim 1 or 2, characterized in that: The particle size of the titanium iron is 30-50 meshes; the particle sizes of the chromium carbide, ferromolybdenum and ferrovanadium are all 80-100 meshes; the particle size of the manganese is 60-80 meshes; the particle size of the ferrosilicon is 70-90 meshes; the particle size of the graphite is 40-60 meshes; and the particle size of the sodium fluoride is 50-70 meshes.
4. A drill pipe joint wear-resistant belt flux-cored welding wire, characterized in that: The raw material comprises the drug core powder according to any one of claims 1 to 3.
5. The drill pipe joint wear-resistant belt flux-cored welding wire according to claim 4, characterized in that: The filling rate of the flux core powder in the flux core welding wire is 22-30%.
6. A welding method for reducing welding porosity of a drill pipe joint wear-resistant belt, characterized in that: The drill pipe joint wear-resistant belt flux-cored welding wire according to claim 4 or 5 is used for welding; the welding process is an arc surfacing process.
7. The welding method according to claim 6, characterized in that: The arc surfacing process parameters are: voltage: 21-24V, current: 280-300A, wire feeding speed: 8-9m / min, atmosphere: 80% Ar+20% CO2 mixed gas, gas flow: 15-20L / min, wire elongation: 15-20mm.
8. The welding method according to claim 6, characterized in that: After the welding is completed, the mass percentage of alloy elements in the obtained cladding metal is within the following ranges: C: 1.40-2.22%, Cr: 11.0-13.4%, Ti: 4.00-7.50%, Si: 1.20-2.00%, Mn: 1.20-2.00%, Mo: 1.20-2.00%, V: 0.20-0.80%, Al: 0.20-1.00%, Fe: balance.
Citation Information
Patent Citations
Grinder roll overlaying dreg-free self-protection flux-cored wire
CN105127614A
Overlaying flux-cored wire for welding and repairing die-casting dies
CN105665959A